Surgical results and outcome of sphenoid wing en plaque meningioma - Mohamed Shaban; Mostafa Abdelsamie; Ahmed Taha (Wolters Kluwer Medknow Publications, 2018)
Background Sphenoid wing en plaque meningioma is a subgroup of meningiomas defined by its particular sheet-like dural involvement and its disproportionately large bone hyperostosis. Sphenoid wing en plaque meningiomas are also called spheno-orbital meningiomas and pterioneal meningiomas en plaque. It represents 2-9% of all meningiomas and they are mainly located in the sphenoid wing. Objective The aim of this study was to analyze the outcome, surgical results, and recurrence rate in a series of 20 patents. Patients and methods This respective descriptive analytical study includes 20 patients with sphenoid wing en plaque meningiomas, who were surgically treated between 2010 and 2014. Results There were 14 women and 6 men, the mean age was 45 years (range: 20 and 70 years), six patients presented by extension of the dural component into the orbit, seven patients with cavernous sinus infiltration, adjuvant radiation therapy was performed for five patients after the surgery. After follow-up at 4 years, seven patients developed tumor recurrence, three patients submitted to surgical treatment, and four patients to radiation therapy. Patients without tumor extension to the orbit or cavernous sinus had the best prognosis, while patients with tumor extension, the recurrent rate was high. Conclusion Postoperative radiation therapy is indicated in cases with residual tumor in cavernous sinus and superior orbital fissure involvement is frequent and should be considered within surgical limits.